A Case Study of Osh Students' Experience with The Use of Virtual Reality as A Learning Media in The Construction Sector at The Public Health Program, Gadjah Mada University - Rahman, Yusuf Mukasyafah Rizqi; Basri, Mubasysyir Hasan; Jaladara, Vena (Green Publisher Indonesia, 2025)
This study explores students' experiences using Virtual Reality (VR) as a learning medium for Occupational Safety and Health (OSH) in the construction sector at the Public Health Study Program, Gadjah Mada University. A qualitative research design with a case study approach was employed, involving 15 participants selected from 43 respondents. Data were collected through in-depth interviews after participants underwent VR OSH training. The analysis revealed that VR provided an engaging and enjoyable learning experience, enhancing students' understanding of safety protocols in hazardous situations. Participants found the VR content relevant and offered practical insights without physical risk. The effectiveness and efficiency of using VR for OSH training were widely recognized, with positive feedback regarding comfort and visual clarity. These findings indicate that VR has the potential to be an innovative tool in OSH education, bridging the gap between theory and practice. The study concludes that integrating VR into higher education curricula can significantly enhance learning experiences and deepen students' understanding of OSH concepts.